Optimal duct layout for HVAC using topology optimization. (16th March 2018) - Manuel, Mark Christian E.; Lin, Po Ting; Chang, Ming
Abstract : Automated design procedure for duct layout has potential for further improving system efficiency. Currently, duct layout is often based on the discretion of the designer and might miss possible areas for energy improvement or meeting system targets, for example, minimal pressure drop, temperature uniformity, and contaminant removal, just to mention a few. Since the initial duct layout design can be considered as a topology problem, topology optimization methods have great potential to advance green building efficiency and design. Topology optimization has been successfully applied to various physics problems, such as structural, heat conduction, and fluidics, yet its application for the built environment, HVAC&R and its subsystems, remains highly unexplored. In the current article, the applicability of topology optimization for determining optimal duct layout is presented. A survey of successfully applied fluid topology optimization cases is presented in the article with outlooks of its applicability to initial duct design. Also, some initial investigations are compared to an existing design. New interpretations are given for intermediate porous flow results in the presented examples. The computational cost of performing large-scale topology optimization is currently one of the biggest limitations of its applicability but with the continuous improvements in computing technology it is indeed a possibility.